SISTEM PENGELOLAAN LAYANAN ARSIP DOKUMEN SKPD DI KOMPLEK PARASAMYA KABUPATEN BANTUL YOGYAKARTA - Witri Anik; Rr. Yuliana Rachmawati K; Catur Iswahyudi (Jurnal SCRIPT, 2015)
A system can facilitate the application of a job if done manually would take a long time, then with the system can help you to work more quickly and more efficiently. SKPDs requires management of archival documents in a neat and structured as currently in handling documents, especially incoming and outgoing mail is still handled manually. Each receives incoming mail is recorded in the book of receipt of the entry manually by employees, and archiving using a control card also entered manually so that the employee is very difficult in case of a double writing on the archive. The existence of the application system can be used to help local government officials in carrying out their duties, which manages incoming and outgoing mail and archive incoming mail and outgoing mail archives in local work unit Bantul Yogyakarta. The result of implementation system to facilitate the work of the employees in carrying out the activity SKPDs correspondence. Implementation of the system is done with management system SKPDs document filing services with PHP and using MySQL database. The results of this study is the implementation of a document archive management system to facilitate the employees in processing incoming and outgoing mail. Also to facilitate employees to store data incoming and outgoing mail that is not susceptible to damage the original document. This system will also help in the management of archives, in archiving incoming and outgoing mail, also will assist in filing a letter automatically when data is 10-year-old letter then it is time data is entered into a data archiving mail letter. Document archive service management system also helps in the process of re-discovery of data and data archives letter letter.